Highly Cytotoxic Copper(II) Mixed-Ligand Quinolinonato Complexes: Pharmacokinetic Properties and Interactions with Drug Metabolizing Cytochromes P450 - Martina Medvedíková; Václav Ranc; Ján Vančo; Zdeněk Trávníček; Pavel Anzenbacher (MDPI AG, 2023)
The effects of two anticancer active copper(II) mixed-ligand complexes of the type [Cu(qui)(mphen)]Y·H2O, where Hqui = 2-phenyl-3-hydroxy- 1H-quinolin-4-one, mphen = bathophenanthroline, and Y = NO3 (complex 1) or BF4 (complex 2) on the activities of different isoenzymes of cytochrome P450 (CYP) have been evaluated. The screening revealed significant inhibitory effects of the complexes on CYP3A4/5 (IC50 values were 2.46 and 4.88 μM), CYP2C9 (IC50 values were 16.34 and 37.25 μM), and CYP2C19 (IC50 values were 61.21 and 77.07 μM). Further, the analysis of mechanisms of action uncovered a non-competitive type of inhibition for both the studied compounds. Consequent studies of pharmacokinetic properties proved good stability of both the complexes in phosphate buffer saline (>96% stability) and human plasma (>91% stability) after 2 h of incubation. Both compounds are moderately metabolised by human liver microsomes (<30% after 1 h of incubation), and over 90% of the complexes bind to plasma proteins. The obtained results showed the potential of complexes 1 and 2 to interact with major metabolic pathways of drugs and, as a consequence of this finding, their apparent incompatibility in combination therapy with most chemotherapeutic agents.